2017
DOI: 10.1080/09602011.2017.1313166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a behaviour management technique for nursing staff on behavioural problems after acquired brain injury

Abstract: The ABC method is a behaviour management technique for use by nurses. ABC refers to the identification of Antecedent events, target Behaviours, and Consequent events. In this longitudinal intervention study with double baseline measurements we evaluated the effectiveness of the ABC method in patients with behavioural problems after acquired brain injury. Fifty-six patients participated in this study. Outcome was measured in terms of overall neuropsychiatric problem behaviour, aggression, apathy and emotional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
(41 reference statements)
0
9
1
Order By: Relevance
“…Beyond necessary compliance to safety regulations and standards in hospital building design and construction, safety management comprises components of occupational health and safety such as infection control, manual handling, and reducing risk of injury. Safety management for both staff and patients in a neurotrauma facility, similar to psychiatric settings, must also incorporate appropriate management of patient neurobehavioral symptoms such as agitation, physical and verbal aggression, irritability, and confusion as a result of the original brain trauma (Williamson et al, 2019; Winkins et al, 2017). A recent systematic review found that agitation occurs in up to 41% of brain injury patients in acute care settings and up to 70% of patients in rehabilitation settings.…”
mentioning
confidence: 99%
“…Beyond necessary compliance to safety regulations and standards in hospital building design and construction, safety management comprises components of occupational health and safety such as infection control, manual handling, and reducing risk of injury. Safety management for both staff and patients in a neurotrauma facility, similar to psychiatric settings, must also incorporate appropriate management of patient neurobehavioral symptoms such as agitation, physical and verbal aggression, irritability, and confusion as a result of the original brain trauma (Williamson et al, 2019; Winkins et al, 2017). A recent systematic review found that agitation occurs in up to 41% of brain injury patients in acute care settings and up to 70% of patients in rehabilitation settings.…”
mentioning
confidence: 99%
“…In addition, patients staying at the departments at the time of the measurements and fulfilled the inclusion criteria (non-progressive ABI, for example traumatic brain injury or stroke, according to medical records, ≥18 years of age, sufficient command of language (by clinical judgement), no post-traumatic amnesia, no decreased consciousness during assessment and giving approval for participation) (Winkens et al, 2019) were included.…”
Section: Methods Participantsmentioning
confidence: 99%
“…This study is part of the long-term follow-up (LT-FU) of our longitudinal group intervention study. The primary goal of our group intervention study was to measure the effect of the ABC method on the behavioural problems of ABI patients (Winkens et al, 2019). A trend was shown towards a decrease of the patients' behavioural problems, albeit not significant.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this analysis, a patient- and situation-tailored intervention is made to reduce challenging behaviour. A more extensive description of the ABC method can be found in Winkens et al [ 10 ].…”
Section: Introductionmentioning
confidence: 99%